2020
DOI: 10.1021/acs.chemmater.0c00078
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Atom Effect of Selenium for Metal-Free Phosphorescent Light-Emitting Diodes

Abstract: Room-temperature phosphorescence from metal-free purely organic molecules has recently gained much interest. We devised metal-free organic phosphors by incorporating selenium (Se) to promote spin–orbit coupling by its nonmetal heavy atom effect. The Se-based organic phosphors showed bright phosphorescent emission in organic light-emitting diodes (OLEDs) and photo-excited phosphorescence in an amorphous film state. Large orbital angular momentum change (ΔL) during the electron transition process and heavy atom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
84
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(98 citation statements)
references
References 62 publications
(101 reference statements)
3
84
0
1
Order By: Relevance
“…To further promote RTP performance and maintain the stimulus response characteristics, a new guest material of N,N,N′,N′‐tetramethylbenzidine (Tmb) was introduced in this study, as it has been reported to show ultralong blue luminescence in rigid environment 21,31–33 . As shown in Figure 1, although no obvious room temperature phosphorescence could be observed for the individual DMAP or Tmb sample, their cocrystal with mass ratio of 400:1 presented efficient blue RTP emission with phosphorescence efficiency and lifetime up to 13.4% and 2.08 s, which has overshadowed most of the organic RTP materials in previous reports 1–23 . Further on, if additional energy acceptor of fluorescein (Fluc) with concentration‐dependent emission was added to construct the ternary cocrystals, the color‐tunable afterglow could be easily realized from blue to yellow through changing the concentrations of Fluc.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…To further promote RTP performance and maintain the stimulus response characteristics, a new guest material of N,N,N′,N′‐tetramethylbenzidine (Tmb) was introduced in this study, as it has been reported to show ultralong blue luminescence in rigid environment 21,31–33 . As shown in Figure 1, although no obvious room temperature phosphorescence could be observed for the individual DMAP or Tmb sample, their cocrystal with mass ratio of 400:1 presented efficient blue RTP emission with phosphorescence efficiency and lifetime up to 13.4% and 2.08 s, which has overshadowed most of the organic RTP materials in previous reports 1–23 . Further on, if additional energy acceptor of fluorescein (Fluc) with concentration‐dependent emission was added to construct the ternary cocrystals, the color‐tunable afterglow could be easily realized from blue to yellow through changing the concentrations of Fluc.…”
Section: Figurementioning
confidence: 99%
“…Particularly, the applications of encryption and bioimaging with RTP materials show a great advantage in comparison with the traditional materials, as the time‐resolved technology could be utilized for their long afterglow after turning‐off the UV irradiation, thus largely promoting the corresponding performance 5–10 . To develop efficient RTP materials, a series of strategies have been explored, such as host–guest interactions, H ‐aggregation, heavy‐atom effect, intermolecular electronic coupling, intermolecular π‐π or hydrogen bond interaction, and so forth 11–18 . Among them, host–guest interactions performed very well 19–23 .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, the ISC process was studied in terms of the orbital angular momentum change, which is related to charge migration from the hole orbital of S 1 to that of T n and from the electron orbital of S 1 to that of T n [37] . Since a similar electron distribution is observed for P(DMPAc‐O‐TPTrz), the ISC between S 1 and T 1 or T 2 involves a certain degree of hole migration from acridine to triazine.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently,the ISC process was studied in terms of the orbital angular momentum change,which is related to charge migration from the hole orbital of S 1 to that of T n and from the electron orbital of S 1 to that of T n . [37] Since asimilar electron distribution is observed for P(DMPAc-O-TPTrz), the ISC between S 1 and T 1 or T 2 involves ac ertain degree of hole migration from acridine to triazine.Herein the introduced O is believed to have two influences.F irst, the dihedral angle between acridine and triazine is up from 29.58 8 of P(DMPAc-TPTrz) to 84.48 8 of P(DMPAc-O-TPTrz) (Supporting Information, Figure S1). Second, attributable to the contributions of not only the lone pairs from Ob ut also the delocalized p electrons from acridine or triazine,S 1 ,T 1 and T 2 bear the hybrid n-p*and p-p*characters.Both the elevated dihedral angle and norbital contribution would induce alarger change of orbital angular momentum in P(DMPAc-O-TPTrz) than in P(DMPAc-TPTrz).…”
Section: Theoretical Calculationsmentioning
confidence: 94%